Primerjava mnenj prebivalcev treh tipov stanovanjskih območij v Kijevu glede kakovosti življenja - Dronova, Olena (Urbani izziv, 2022)
According to Global North urban studies, the traditional low-rise mixed-function perimeter block is the most attractive urban morphology in terms of organization of space, time, values, and social interactions. This study examines how valid these basic theses are regarding the comfort of urban housing morphological types in Kyiv, the capital of Ukraine. We compare residents’ quality of life and analyse the differences in residents’ behavioural patterns and spatial perception in different morphological types of housing to identify distinguishing features of the most comfortable urban form. Using expert evaluation and surveys, we assess history; jobs; social, educational, and cultural services; environmental indicators; security levels; and public activity in three different neighbourhoods: Zhulyany (with detached houses), Podil (with low-rise perimeter blocks), and Rusanivka (with Soviet high-rises). The results reveal that the Soviet neighbourhood, Rusanivka, leads in terms of both objective indicators and residents’ perception as the most comfortable living area. This finding contradicts generally accepted theories about exemplary and attractive urban morphology. This preference is based on the planning and construction priorities of the unique social system of Rusanivka, where its human-centeredness and a thoughtful integrated approach are highly valued.
Keywords: kakovost življenja; Kijev; Kyiv; neighbourhoods; perceptions; quality of life; stanovanjske soseske; urban morphology; urbana morfologija; zaznave